2020
DOI: 10.1038/s41598-020-69509-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale reconstruction of Paenarthrobacter aurescens TC1 metabolic model towards the study of atrazine bioremediation

Abstract: Atrazine is an herbicide and a pollutant of great environmental concern that is naturally biodegraded by microbial communities. Paenarthrobacter aurescens TC1 is one of the most studied degraders of this herbicide. Here, we developed a genome scale metabolic model for P. aurescens TC1, iRZ1179, to study the atrazine degradation process at organism level. Constraint based flux balance analysis and time dependent simulations were used to explore the organism's phenotypic landscape. Simulations aimed at designing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Microorganisms that grow in environments with extreme pH, salinity, and temperature conditions are also important sources of lipases with industrial potential [23]. Paenarthrobacter aurescens TC1 (formerly Arthrobacter aurescens TC1) is a high G+C content Gram-positive aerobic bacterium that acts as a bacterial bioremediate to degrade the herbicide atrazine and has been shown to degrade most other common amino acids [24][25][26]. Due to the presence of duplicated catabolic genes and its ability to funnel plasmid-derived intermediates into chromosomally encoded pathways, the P. aurescens strain can survive and prosper under various pressure and temperature conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms that grow in environments with extreme pH, salinity, and temperature conditions are also important sources of lipases with industrial potential [23]. Paenarthrobacter aurescens TC1 (formerly Arthrobacter aurescens TC1) is a high G+C content Gram-positive aerobic bacterium that acts as a bacterial bioremediate to degrade the herbicide atrazine and has been shown to degrade most other common amino acids [24][25][26]. Due to the presence of duplicated catabolic genes and its ability to funnel plasmid-derived intermediates into chromosomally encoded pathways, the P. aurescens strain can survive and prosper under various pressure and temperature conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, an Arthrobacter species (NCBI accession MG554188 ) was identified as an efficient degrader of atrazine in soil taken from a commercial field in Newe-Ya’ar, Israel ( 32 ). The native species is highly similar (98% identity) to the well-studied atrazine degrader Paenarthrobacter aurescens TC1 ( 34 , 39 , 40 ). Despite clear evidence for atrazine degradation activity in general and in the specific soil in particular, the relative abundance of the Arthrobacter species was unaffected by application of atrazine at conventional rates in commercial agricultural practices ( 32 ).…”
Section: Resultsmentioning
confidence: 89%
“…S1 ). The amino acids include serine, an efficient biostimulant among amino acids, and histidine, whose simulative effect depends on the presence of atrazine (and is more significant in its absence) ( 34 ). OCDCA, despite being a carbon-rich compound, is predicted to be a nonefficient enhancer, indicating that the number of carbons by itself is insufficient for predicting simulation efficiency ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial remediation of contaminated soil have become a popular choice because of their relatively low application cost and minimal environmental impact [ 5 , 6 ]. At present, certain degrading bacteria have been isolated and applied in remediating atrazine – contaminated soil [ 7 , 8 ], including strains of Pseudomonas sp. [ 9 ], Rhodococcus sp .…”
Section: Introductionmentioning
confidence: 99%